Structured Abstract Adoption in Nursing Journals: Trends and Disciplinary Differences - Sayo Nanami; Tomomi Sasaki (JALT Postconference Publication, 2026)
This study investigates the historical adoption of structured abstracts (SA) in nursing journals from 1950 to 2024. Specifically, it examines changes in SA prevalence over time and across journal types and disciplinary orientations. Drawing on 6,604 articles from nine journals, the study identifies three phases of SA adoption: emergence in the 1990s, rapid expansion in the 2000s, and stabilization after 2010. Adoption varied considerably among journals. Those closely aligned with clinical medicine adopted SA earlier and more consistently, whereas journals with broader interdisciplinary or qualitative orientations showed slower uptake. These findings suggest that SA has become a widely accepted feature of scholarly communication in health-related fields while continuing to reflect disciplinary differences in research traditions and publishing practices. The study provides a longitudinal account of SA adoption and highlights its relevance to the standardization of academic communication and EAP instruction. 本研究では、1950年から2024年までの看護学関連ジャーナルにおける構造化抄録（SA）の導入動向を検討した。特に、SA の採用率が時間の経過とともにどのように変化したか、またジャーナルの種類や学問分野の特性によってどのような違いがみられるかを分析した。9誌・6,604本の論文を分析した結果、SAの導入には、1990年代の導入期、2000年代の急速な普及期、2010年以降の定着期という3つの段階が確認された。ジャーナル間には顕著な差異がみられ、臨床医学との関連が強いジャーナルでは早期かつ一貫した導入が進んだ一方、学際的あるいは質的研究を多く扱うジャーナルでは導入が緩やかであった。これらの結果は、SAが保健医療系分野の学術コミュニケーションに広く定着している一方で、その導入状況が分野ごとの研究・出版慣行の違いを反映していることを示す。本研究は、SA導入の長期的推移を明らかにし、学術コミュニケーションの標準化やEAP 教育への示唆を提供する。